Higher order aberrations in amblyopic children and their role in refractory amblyopia - Dias-Santos,Arnaldo (2014)
Objective: Some studies have hypothesized that an unfavourable higher order aberrometric profile could act as an amblyogenic mechanism and may be responsible for some amblyopic cases that are refractory to conventional treatment or cases of “idiopathic” amblyopia. This study compared the aberrometric profile in amblyopic children to that of children with normal visual development and compared the aberrometric profile in corrected amblyopic eyes and refractory amblyopic eyes with that of healthy eyes. Methods: Cross-sectional study with three groups of children – the CA group (22 eyes of 11 children with unilateral corrected amblyopia), the RA group (24 eyes of 13 children with unilateral refractory amblyopia) and the C group (28 eyes of 14 children with normal visual development). Higher order aberrations were evaluated using an OPD-Scan III (NIDEK). Comparisons of the aberrometric profile were made between these groups as well as between the amblyopic and healthy eyes within the CA and RA groups. Results: Higher order aberrations with greater impact in visual quality were not significantly higher in the CA and RA groups when compared with the C group. Moreover, there were no statistically significant differences in the higher order aberrometric profile between the amblyopic and healthy eyes within the CA and RA groups. Conclusions: Contrary to lower order aberrations (e.g., myopia, hyperopia, primary astigmatism), higher order aberrations do not seem to be involved in the etiopathogenesis of amblyopia. Therefore, these are likely not the cause of most cases of refractory amblyopia.